ANALISA..TINGKAT..EFEKTIVITAS..PENERIMAAN..PAJAK..BUMI.. DAN BANGUNAN PERDESAAN DAN PERKOTAAN.. DI..KABUPATEN BARITO SELATAN - Deswandy Andrean Wicaksono; Sufi Jikrilah (Universitas Lambung Mangkurat, 2021)
This research..aims to analyze how far the effectiveness of receiving Rural and Urban Land and Building Tax in South Barito Regency. The research shows that the effectiveness of PBB-P2 in the last 5 years is categorized as quite effective and with various efforts made BPKAD of Barito..South..Regency to continue to increase revenue of land and building tax in rural and urban areas.